Developer's guide to web application security - Cross, Michael, 1965- (Syngress Pub., 2007)
Over 75% of network attacks are targeted at the web application layer. This book provides explicit hacks, tutorials, penetration tests, and step-by-step demonstrations for security professionals and Web application developers to defend their most vulnerable applications. This book defines Web application security, why it should be addressed earlier in the lifecycle in development and quality assurance, and how it differs from other types of Internet security. Additionally, the book examines the procedures and technologies that are essential to developing, penetration testing and releasing a secure Web application. Through a review of recent Web application breaches, the book will expose the prolific methods hackers use to execute Web attacks using common vulnerabilities such as SQL Injection, Cross-Site Scripting and Buffer Overflows in the application layer. By taking an in-depth look at the techniques hackers use to exploit Web applications, readers will be better equipped to protect confidential. * The Yankee Group estimates the market for Web application-security products and services will grow to $1.74 billion by 2007 from $140 million in 2002 * Author Matt Fisher is a highly sought after speaker who regularly delivers Web Application presentations at leading conferences including: Black Hat, TechnoSecurity, CanSec West, Shmoo Con, Information Security, RSA Conferences, and more * The Companion Web site will have downloadable code and scripts presented in the book.